2017
DOI: 10.3389/fpls.2017.00956
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Avocado Hass (Persea americana Mill) in the Interaction System Fruit-Chitosan-Colletotrichum

Abstract: Avocado (Persea americana) is one of the most important crops in Mexico as it is the main producer, consumer, and exporter of avocado fruit in the world. However, successful avocado commercialization is often reduced by large postharvest losses due to Colletotrichum sp., the causal agent of anthracnose. Chitosan is known to have a direct antifungal effect and acts also as an elicitor capable of stimulating a defense response in plants. However, there is little information regarding the genes that are either ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 46 publications
(54 reference statements)
2
36
0
3
Order By: Relevance
“…Although mechanism of chitosan induced higher fruit yield and accumulation of antioxidants in strawberry fruit are not explored in the current study, we propose a hypothetical pathway in Fig 4 . A further study is needed for validation of our proposed hypothesis [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mechanism of chitosan induced higher fruit yield and accumulation of antioxidants in strawberry fruit are not explored in the current study, we propose a hypothetical pathway in Fig 4 . A further study is needed for validation of our proposed hypothesis [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent transcriptomic analysis reveals that chitosan induces expression of genes involved in multiple physiological processes including systemic acquired resistance, plant immune system, photosynthesis and hormone metabolism. It also influenced expression of heat-shock protein and re-programming of protein metabolism with an increment of storage proteins [ 22 , 23 ]. However, information on field application of chitosan for enhancing yield and human health benefiting biochemical contents in small fruit is scant.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological mechanisms of the fruit are positively affected by the application of chitosan at post-harvest management under biotic and abiotic stress, that is why the post-harvest shelf-life and quality (firmness, appearance, color) of fruit can be maintained during the storage time, besides the respiration rate and ethylene production of fruits decrease [31]. Some studies reported an enhanced content of total soluble solids, ascorbic acid, the nutritional value, and acceptability [30,32,33]. Chitosan is compatible with other substances like organic salts, gums, or essential oils, and this alternative can improve their efficacy against pathogens due to a synergistic effect [34,35].…”
Section: Chemical Methods: Applications For Post-harvest Disease Manamentioning
confidence: 99%
“…Chitosan has been widely used as a coating agent of various fruits mainly for protection from postharvest losses, enhancing the storability and preservation [9,[14][15][16][17][18]. A large body of literature indicates that foliar application of CHT increases vegetative growth, yield and induces synthesis of secondary metabolites, such as polyphenolics, lignin, flavonoids, and phytoalexins in plants [19][20][21][22][23]. It also promotes expression of genes involved in hormone metabolism, photosynthesis, the plant immune system, heat-shock proteins, systemic acquired resistance, and reprogramming of protein metabolism with an increment of storage proteins [24,25].…”
Section: Fundingmentioning
confidence: 99%